Dye‐Enhanced Multimodal Confocal Imaging as a Novel Approach to Intraoperative Diagnosis of Brain Tumors. (28th August 2012) - Snuderl, Matija; Wirth, Dennis; Sheth, Sameer A.; Bourne, Sarah K.; Kwon, Churl‐Su; Ancukiewicz, Marek; Curry, William T.; Frosch, Matthew P.; Yaroslavsky, Anna N.
Abstract: Intraoperative diagnosis plays an important role in accurate sampling of brain tumors, limiting the number of biopsies required and improving the distinction between brain and tumor. The goal of this study was to evaluate dye‐enhanced multimodal confocal imaging for discriminating gliomas from nonglial brain tumors and from normal brain tissue for diagnostic use. We investigated a total of 37 samples including glioma (13), meningioma (7), metastatic tumors (9) and normal brain removed for nontumoral indications (8). Tissue was stained in 0.05 mg/mL aqueous solution of methylene blue (MB) for 2–5 minutes and multimodal confocal images were acquired using a custom‐built microscope. After imaging, tissue was formalin fixed and paraffin embedded for standard neuropathologic evaluation. Thirteen pathologists provided diagnoses based on the multimodal confocal images. The investigated tumor types exhibited distinctive and complimentary characteristics in both the reflectance and fluorescence responses. Images showed distinct morphological features similar to standard histology. Pathologists were able to distinguish gliomas from normal brain tissue and nonglial brain tumors, and to render diagnoses from the images in a manner comparable to haematoxylin and eosin (H&E) slides. These results confirm the feasibility of multimodal confocal imaging for intravital intraoperative diagnosis.